Prevention and management of CMV infections after liver transplantation: current practice in German transplant centers - Engelmann, Cornelius; Sterneck, Martina; Weiss, Karl Heinz; Templin, Silke; Zopf, Steffen; Denk, Gerald Ulrich; Eurich, Dennis; Pratschke, Johann; Weiß, Johannes; Braun, Felix; Welker, Martin-Walter; Zimmermann, Tim; et al. (Journal of Clinical Medicine, 2020)
Human cytomegalovirus (CMV) remains a major cause of mortality and morbidity in human liver transplant recipients. Anti-CMV therapeutics can be used to prevent or treat CMV in liver transplant recipients, but their toxicity needs to be balanced against the benefits. The choice of prevention strategy (prophylaxis or preemptive treatment) depends on the donor/recipient sero-status but may vary between institutions. We conducted a series of consultations and roundtable discussions with German liver transplant center representatives. Based on 20 out of 22 centers, we herein summarize the current approaches to CMV prevention and treatment in the context of liver transplantation in Germany. In 90% of centers, transient prophylaxis with ganciclovir or valganciclovir was standard of care in high-risk (donor CMV positive, recipient CMV naive) settings, while preemptive therapy (based on CMV viremia detected during (bi) weekly PCR testing for circulating CMV-DNA) was preferred in moderate- and low-risk settings. Duration of prophylaxis or intense surveillance was 3–6 months. In the case of CMV infection, immunosuppression was adapted. In most centers, antiviral treatment was initiated based on PCR results (median threshold value of 1000 copies/mL) with or without symptoms. Therefore, German transplant centers report similar approaches to the prevention and management of CMV infection in liver transplantation.
Gesehen am 15.03.2020